Model Sistem Informasi Pengelolaan Absensi dan Penggajian Berbasis Web Pada PT Sekawan Mitra Kreasi - Kristanti, Ayu; Rusmawan, Uus (STMIK Banjarbaru, 2023)
The process of managing attendance and payroll with a large volume of data at PT Sekawan Mitra Kreasi raises problems related to the effectiveness and efficiency of the process as a result of a work system that is still manual. This study aims to develop a management and payroll information system model to improve employee discipline and payroll calculations that are precise and efficient. Web attendance data makes it easy to record attendance and calculate employee salaries and add each employee's work model. The presence of PT Sekawan Mitra Kreasi staff and payment for work is done through data collection, system analysis, design and operation. Based on the analysis of interviews and observations, it is very important to ensure speed, accuracy and economy in the process of calculating employee salaries. Thus, the right of workers to receive wages from the system created by the creator will not be affected. The system was built following the general procedures of the System Development Life Cycle (SDLC) using the PHP Programming Language in the Laravel Framework. System functions include managing attendance and calculating employee salaries, with employees taking attendance when entering and returning from work, from the reslts of employee attendance that have been stored in the system, HRD performs calculations and inputs employee salary nominal in the system, Employees can see the nominal salary in received through the system and tested through Blackbox Testing. The test results show that all functional features work validly.Keywords: System; attendance; payroll; Employee; XAMPPÂ AbstrakProses pengelolaan absensi dan penggajian dengan volume data yang besar pada PT Sekawan Mitra Kreasi, menimbulkan masalah terkait efektivitas dan efisiensi proses sebagai akibat dari sistem kerja yang masih manual. Penelitian ini bertujuan mengembangkan model sistem informasi pengelolaan dan penggajian untuk dapat meningkatkan ke disiplinan karyawan serta penghitungan gaji yang tepat dan efisien. Data absensi web memudahkan untuk mencatat kehadiran dan menghitung gaji karyawan serta menambahkan model kerja masing-masing karyawan. Kehadiran staf PT Sekawan Mitra Kreasi dan pembayaran pekerjaan dilakukan melalui pengumpulan data, analisis sistem, desain dan pengoperasian. Berdasarkan analisis wawancara dan observasi, sangat penting untuk memastikan kecepatan, ketepatan dan penghematan dalam proses penghitungan gaji karyawan. Dengan demikian, hak pekerja untuk menerima upah dari sistem yang dibuat oleh pencipta tidak akan terpengaruh. Sistem dibangun mengikuti prosedur umum System Development Life Cycle (SDLC) dengan menggunakan Bahasa Pemrograman PHP dalam Framework Laravel. Fungsi-fungsi sistem berupa pengelolaan absensi dan penghitungan gaji karyawan, dengan karyawan melakukan absensi saat masuk dan pulang kerja, dari hasil absensi karyawan yang telah tersimpan pada sistem, HRD melakukan penghitungan dan input nominal gaji karyawan pada sistem, Karyawan dapat melihat nominal gaji yang di terima melalui sistem dan diuji melalui Uji Balckbox Testing. Hasil uji menunjukkan seluruh fitur fungsional telah bekerja secara valid.Â